Recent Progress and Approaches on Transition Metal Chalcogenides for Hydrogen Production - Shanmugaratnam, S.; Yogenthiran, E.; Koodali, R.; Ravirajan, P.; Velauthapillai, D.; Shivatharsiny, Y. (Energies, 2021)
Development of efficient and affordable photocatalysts is of great significance for energy production and environmental sustainability. Transition metal chalcogenides (TMCs) with particle sizes in the 1–100 nm have been used for various applications such as photocatalysis, photovoltaic, and energy storage due to their quantum confinement effect, optoelectronic behavior, and their stability. In particular, TMCs and their heterostructures have great potential as an emerging inexpensive and sustainable alternative to metal-based catalysts for hydrogen evolution. Herein, the methods used for the fabrication of TMCs, characterization techniques employed, and the different methods of solar hydrogen production by using different TMCs as photocatalyst are reviewed. This review provides a summary of TMC photocatalysts for hydrogen production.
Keywords: transitionmetal chalcogenides; hydrogen production; photocatalysis; apparent quantumyield